2020
DOI: 10.1097/paf.0000000000000601
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Death Due to Severe Ovarian Hyperstimulation Syndrome

Abstract: Ovarian hyperstimulation syndrome (OHSS) is a rare iatrogenic disorder associated with controlled ovarian stimulation during assisted reproductive technology. Severe OHSS may impose serious complications, including pleural effusion, acute renal insufficiency, venous thrombosis, and even death, although lethal outcomes are rare in forensic practice. The reported incidence of severe OHSS ranges from 0.008% to 10%. Herein, we present the case of a 29-year-old woman who diagnosed with polycystic ovary syndrome and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…10 Although all patients in these case reports eventually recovered after intensive treatment, it is important to note that in severe cases, OHSS can be a life-threatening condition that requires immediate medical attention and intervention to prevent serious complications such as thromboembolism, renal failure, and respiratory distress syndrome. 24,25 In this context, it is important to consider the potential risks associated with the use of longacting GnRHa as an ovulation trigger in patients undergoing COH, particularly in the setting of cancer treatment. One study suggested the use of this approach, 17 but it may not be appropriate for cancer patients who need to start treatment as soon as possible to achieve optimal results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Although all patients in these case reports eventually recovered after intensive treatment, it is important to note that in severe cases, OHSS can be a life-threatening condition that requires immediate medical attention and intervention to prevent serious complications such as thromboembolism, renal failure, and respiratory distress syndrome. 24,25 In this context, it is important to consider the potential risks associated with the use of longacting GnRHa as an ovulation trigger in patients undergoing COH, particularly in the setting of cancer treatment. One study suggested the use of this approach, 17 but it may not be appropriate for cancer patients who need to start treatment as soon as possible to achieve optimal results.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Although all patients in these case reports eventually recovered after intensive treatment, it is important to note that in severe cases, OHSS can be a life-threatening condition that requires immediate medical attention and intervention to prevent serious complications such as thromboembolism, renal failure, and respiratory distress syndrome. 24 , 25 …”
Section: Discussionmentioning
confidence: 99%
“… 12 - 15 However, no fatal case has been reported yet. Wang et al 16 reported the sudden death of a 29-year-old woman due to severe ovarian hyperstimulation syndrome in the aftermath of assisted reproduction technology and ovarian puncture. At autopsy, turbid effusions of pleural and peritoneal cavities, abnormal ovarian enlargement, and duskiness of multiple organ surfaces were observed.…”
Section: Discussionmentioning
confidence: 99%
“…The development of OHSS may necessitate delaying critical cancer treatments, which can affect patients’ prognosis [ 40 , 41 ]. While OHSS is usually manageable with intensive medical intervention, its severe manifestations carry significant risks, including thromboembolism, renal failure, and respiratory distress syndrome [ 42 ].…”
Section: Ohss In Cancer Patients Referred For Fertility Preservationmentioning
confidence: 99%